PUSAT INFORMASI GEOPARK MERATUS DI BANJARBARU - Cahyadi, Muhammad Rizqon; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Meratus Geopark is a government program to preserve the Meratus Mountains. These mountains stretch from the southeast to the northwest of South Kalimantan Province. These mountains have biodiversity and non-biological diversity which in recent years has been massively exploited to the point of environmental degradation. To reduce and anticipate environmental damage, the local government cooperates with various parties to initiate the Meratus Geopark program. In 2019, Geopark Meratus succeeded in becoming part of Geopark Indonesia, but until now there is no Meratus Geopark Information Center available. The Meratus Geopark Information Center is planned to be built in Pumpung Cempaka Village which is known as one of the largest diamond mining villages in South Kalimantan. The architectural problem to be solved is